Cardiovascular prevention in women: a narrative review from the Italian Society of Cardiology working groups on 'Cardiovascular Prevention, Hypertension and peripheral circulation' and on 'Women Disease'. Issue 9 (September 2019) - Mattioli, Anna Vittoria; Sciomer, Susanna; Moscucci, Federica; Maiello, Maria; Cugusi, Lucia; Gallina, Sabina; Dei Cas, Alessandra; Lombardi, Carolina; Pengo, Martino; Parati, Gianfranco; Barilla, Francesco; Ciccone, Marco Matteo; et al.
Abstract : N/A: Cardiovascular disease (CVD) is the leading cause of mortality and morbidity in women. Some authors highlighted that the female risk profile consists of traditional and emerging risk factors. Despite the lower prevalence of type 2 diabetes, years of life lost owing to the disease for women are substantially higher compared with men. In addition, pregnancy complicated by gestational diabetes represents a risk factor for CVD. Women with gestational diabetes have a higher prevalence of coronary artery disease that occur at a younger age and are independent of T2DM. Hypertension is an important cardiovascular risk factor in women. Estrogens and progesterone, known to have an impact on blood pressure levels, have also been proposed to be protective against sleep-disordered breathing. It is very difficult to understand whereas obstructive sleep apnea in women is independently as sociated with hypertension or if many confounders acting at different stages of the woman lifespan mediate this relation. The cardioprotective effect of physical activity in women of all ages is well known. Women are generally more physically inactive than men. During and after menopause, most women tend to reduce their physical activity levels and together with the reduction in basal metabolic rate, women experience loss of skeletal muscle mass with a negative change in the ratio of fat-to-lean mass. In conclusion, sex differences in the cardiovascular system are because of dissimilarities in gene expression and sex hormones; these result in variations in prevalence and presentation of CVD and associated conditions, such as diabetes, hypertension and vascular and cardiac remodeling. Changes in lifestyle and increase in physical activity could help in prevention of cardiovascular disease in women.